Ο ρουμάνος ηγεμόνας Μιχαήλ ο Γενναίος (1593-1601) και οι Έλληνες - DINU, TUDOR (Μνήμων, 2011)
The present work constitutes a detailed study of the relations between the Romanian Prince Michael the Brave (1593-1601) and the Greek world of his time. From our research it follows that Michael was the son of a Greek by the name of Yannis the Epirot, a person of great influence in the Ottoman Court, where he was holding the dignity of representative for the Romanian Lands. From a young age Michael had close links to the Cantacuzin family that helped him come to power, and to which he consequently proved faithful over time. In line with his anti-Ottoman policy, the prince proved hostile to the Greek elements subordinated to the Sultan’s power, but would offer, by his often humble means, his support for several Greek rebel leaders, plotting against the Turkish rule (Dionysios Rallis Palaeologos, Metropolitan of Târnovo, Athanasios, Archbishop of Ohrid, Dionysios Bishop of Larisa and Trikala). Benefiting from Michael’s help were also those Greek prelates that fought against the attempted union of the orthodox to the Romanian Church, e. g. Nikephoros Daskalos. Moreover, the Romanian ruler chose to send Greek emissaries for several of his own diplomatic missions (to Poland and Russia). The need for a temporary truce with the Turks to reinforce his armies that had been weakened by wars, pushed him to resort to the mediation of some high orthodox hierarchs fully vassal to the Porte, such as Meletios Pigas, patriarch of Alexandria. Also, in the ranks of the Romanian Prince’s army the presence of Greek mercenaries has been confirmed, though of lesser importance than the one of other subjugated Balkan peoples (Serbians, Bulgarians, Albanians). Michael’s victories against the Turks resounded loudly in the conscience of the subjugated Greeks and led to the composition of two literate poems (by Stavrinos and Palamedes) and of several folk songs extolling the supposed liberator from the Ottoman yoke. In relation to these, in the present paper we have analysed the reasons behind Michael’s adoption by the Greeks as a real national hero and studied the prince’s image, as depicted in the two literary works.